Astraeus I: the interplay between galaxy formation and reionization. Issue 3 (3rd March 2021) - Hutter, Anne; Dayal, Pratika; Yepes, Gustavo; Gottlöber, Stefan; Legrand, Laurent; Ucci, Graziano
ABSTRACT: We introduce a new self-consistent model of galaxy evolution and reionization, astraeus (seminumerical rA diative tranS fer coupling of galaxy formaT ion and R eionization in N -body dA rk mattE r simU lationS ), which couples a state-of-the-art N -body simulation with the semi-analytical galaxy evolution delphi and the seminumerical reionization scheme cifog. astraeus includes all the key processes of galaxy formation and evolution (including accretion, mergers, supernova, and radiative feedback) and follows the time and spatial evolution of the ionized regions in the intergalactic medium (IGM). Importantly, it explores different radiative feedback models that cover the physically plausible parameter space, ranging from a weak and delayed to a strong and immediate reduction of gas mass available for star formation. From our simulation suite that covers the different radiative feedback prescriptions and ionization topologies, we find that radiative feedback continuously reduces star formation in galaxies with $M_ h\lesssim 10^{9.5}\, {\rm \rm M_\odot }$ upon local reionization; larger mass haloes are unaffected even for the strongest and immediate radiative feedback cases during reionization. For this reason, the ionization topologies of different radiative feedback scenarios differ only on scales smaller than 1–2 comoving Mpc, and significant deviations are found only when physical parameters (e.g. the escape fraction of ionizing photons) are altered based on galactic properties. Finally, we find that observables (the ultraviolet luminosity function, stellar mass function, reionization histories and ionization topologies) are hardly affected by the choice of the used stellar population synthesis models that model either single stars or binaries.